Hydatidiform mole in Duhok, Iraq: Frequency, types and histopathological diagnostic features - Matlob, Rana Mumtaz; Ilias Yalda, Mayada; Hussein, Zihel Hassan; Faraj, Tamara Qais (Journal of Surgery and Medicine, 2020)
Aim: There is a worldwide variation in the distribution of molar pregnancy with respect to its type. Difficulties in obtaining accurate data about miscarriage make the precise incidence uncertain. The aim of this study was to estimate the frequency of Hydatidiform mole among the miscarriages and deliveries in Duhok province, estimate their main types, partial or complete, and correlate them with histopathological diagnostic features. Methods: This cross-sectional study was conducted between June 1, 2016 and September 1, 2019 and included Hydatidiform mole cases from the main histopathological centers in Duhok and Zakho. All childbirths and miscarriages were evaluated within the same areas and during the same period. Samples were examined histologically and divided into three groups as partial, complete, and indeterminate molar types, after which their correlation with the main histopathological features were examined. Additional efforts were made to identify the indeterminate cases, like the use of P57 marker. Results: The frequency of Hydatidiform mole was less than 1%. Complete type represented 43% of the cases with a relatively high percentage of indeterminate molar pregnancies (26%). The highest percentage of women belonged to the 20-30 years-old group. The most common histological feature was circumferential trophoblastic proliferation. Conclusion: The frequency of Hydatidiform mole in Duhok was within the world range, with a relatively high percentage of indeterminate types. More efforts should be made to establish an accurate diagnosis depending on histopathological features and additional markers like P57 should be used.